2014
DOI: 10.1371/journal.pone.0090616
|View full text |Cite
|
Sign up to set email alerts
|

Mating Systems, Reproductive Success, and Sexual Selection in Secretive Species: A Case Study of the Western Diamond-Backed Rattlesnake, Crotalus atrox

Abstract: Long-term studies of individual animals in nature contribute disproportionately to our understanding of the principles of ecology and evolution. Such field studies can benefit greatly from integrating the methods of molecular genetics with traditional approaches. Even though molecular genetic tools are particularly valuable for species that are difficult to observe directly, they have not been widely adopted. Here, we used molecular genetic techniques in a 10-year radio-telemetric investigation of the western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 88 publications
1
65
0
Order By: Relevance
“…mammals : Carling, Wiseman & Byers, 2003;birds: Gowaty & Karlin, 1984;fish: Soucy & Travis, 2003); insects (Boomsa, Fjerdingstad & Frydenberg, 1999), and A. contortrix under laboratory conditions (Schuett & Gillingham, 1986)], our findings are novel for wild copperhead, and only the second for New World pitvipers (Jellen & Aldridge, 2011;Clark et al, 2014). Multiple paternity may occur under several scenarios: when females mate multiply within a single season or when long-term sperm storage from different males is maintained across breeding seasons, or a combination of the two (Uller & Olsson, 2008;Jellen & Aldridge, 2011).…”
Section: Parentage Analyses and Multiple Paternitymentioning
confidence: 70%
See 1 more Smart Citation
“…mammals : Carling, Wiseman & Byers, 2003;birds: Gowaty & Karlin, 1984;fish: Soucy & Travis, 2003); insects (Boomsa, Fjerdingstad & Frydenberg, 1999), and A. contortrix under laboratory conditions (Schuett & Gillingham, 1986)], our findings are novel for wild copperhead, and only the second for New World pitvipers (Jellen & Aldridge, 2011;Clark et al, 2014). Multiple paternity may occur under several scenarios: when females mate multiply within a single season or when long-term sperm storage from different males is maintained across breeding seasons, or a combination of the two (Uller & Olsson, 2008;Jellen & Aldridge, 2011).…”
Section: Parentage Analyses and Multiple Paternitymentioning
confidence: 70%
“…Long-term sperm storage has been documented in A. contortrix and other snakes (Booth & Schuett, 2011) and could result in offspring being sired by males that mated with females in previous seasons. Furthermore, the cryptic coloration and behaviours of many snakes (Shine, 2008), including copperhead, may permit copulation without human detection (Clark et al, 2014), even in well documented and observed populations ).…”
Section: Opportunities For Selection and Sexual Selectionmentioning
confidence: 99%
“…In early spring, sperms are expelled out from the oviduct to fertilize with oocyte shortly after subsequent spring mating. Many reports have explained that reptiles have two distinct mating seasons prior to ovulation, e.g., Thamnophis sirtalis in Michigan, Bothrops neuwiedi in Brazil, and Crotalus atrox in Arizona (Schwartz et al 1989;Hartmann et al 2004;Clark et al 2014). Fertilization in spring ensures that eggs are laid in the middle of rainy seasons.…”
Section: Resultsmentioning
confidence: 99%
“…Taxon biases are even found within reptiles, with far less information available on snakes, for instance, than in other lineages (Bonnet, Shine & Lourdais, ; Shine, ). Secretiveness, cryptic habits, rarity, and small body size play a significant role in explaining this historic gap of information in snakes (Bonnet et al ., ; Clark et al ., ). Nonetheless, in recent years, radio‐telemetry has circumvented many logistical problems in locating and observing wild individuals for extended periods (Reinert, ; Dorcas & Willson, ).…”
Section: Introductionmentioning
confidence: 97%